Comparative Analysis of Digital Application Usage in Micro Enterprises and Small Medium Enterprises - Abdurrahman Rahim Thaha; Agus Santosa; Aji Fajar Suryo Antoro (PT Mattawang Mediatama Solution, 2023)
This study aims to analyze the factors that influence the use of digital applications in Micro Enterprises (UMi) and Small and Medium Enterprises (SMEs/UKM) in Indonesia, using the TOE (Technology-Organization-Environment) framework. Through a quantitative approach, this study collected data from 426 MSMEs and analyzed it using the Partial Least Square-Structural Equation Modelling (PLS-SEM) model. The results show that technological factors are the dominant factors in the use of digital applications in MSMEs. However, there are significant differences in the influence of these factors between UMi and UKM. In UMi, technological factors are more prominent, while in UKM, organizational factors are more influential as determinants of digital application use. UMi focuses more on the technological aspect of digital app usage, while UKM prioritize organization as the main driver. This study provides important insights into the dynamics of digital app usage among MSMEs and the strategic differences between UMi and UKM, offering guidance for the development of more effective and scale-appropriate technology strategies.